Determinasi modal intelektual, ukuran perusahaan, struktur modal terhadap harga saham dengan kinerja keuangan sebagai intervening - Mia Laksmiwati; Retno Fuji Oktaviani; Rinny Meidiyustiani; Sugeng Priyanto (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
The main objective of this paper is to examine the effect of intellectual capital, company size, and capital structure on stock prices and their impact on financial performance as intervening variables. This paper uses the Partial Least Square (PLS) approach using Smart PLS software. The analysis in this paper consists of two measurement models, the outer model or measurement model and the inner model or structural model. The number of companies used as research samples was 16 during the 2017-2021 period in Badan Usaha Milik Negara (BUMN). The results of the study show that Intellectual Capital has a significant and positive effect on stock prices and also a significant and positive effect on financial performance. Capital structure has no significant effect on stock prices and has a significant and positive effect on financial performance. Company size has no significant effect on stock prices and has a significant and positive effect on financial performance. Financial performance has a significant and positive effect on stock prices.